Feeding and habitat of slow Loris (Nycticebus coucang) in Badui Tribe conservation forest, Rangkasbitung-south Banten - WIRDATETI WIRDATETI; LILIK ENDANG SETYORINI; SUPARNO SUPARNO; TRI HADI HANDAYANI (Biodiversitas Journal of Biological Diversity, 2005)
Feeding and habitat of slow Loris (Nycticebus coucang) in conservation forest located in Rangkasbitung-South Banten has been studied. This study was conducted in protected forest of the Paniga and Kiaralawang Baduy tribe in Cibeo for the inner Baduy and in Tinjoleat forest for the outer Baduy. The Study site was located about 250-610 m above sea level. The collected data consist of the type of feeding, nest sites and health. During the observation there were 61 plant species from 24 families which were dominated by Moraceae and Euphorbiaceae were consumed by slow Loris. Six other kinds of feed consist of small animals: reptile, mammals, aves, and insects. Nestwas building on host plant from growing trees and made of litters.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Nycticebus coucang, slow loris, Rangkasbitung conservation forest.